Propagation of a photoinduced surface wave along an ideal metalphotorefractive crystal interface - Rafael Torres-Cordoba (Revista Mexicana de Física, 2005)
A mathematical model is developed in order to study self-confinement of the square beam propagating along the boundary of the IdealMetal-Photorefractive Crystal media. It is shown that the square beam is self-bending and can be balanced by internal reflection at thePhotorefractive Crystal surface to result in surface wave formation. Theoretical evidence is given.